2019
DOI: 10.17759/psyedu.2019110310
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Pedagogical Support for Students with Disabilities in Inclusive Educational Environment of University

Abstract: The authors analyze the components of psychological and pedagogical support for students with disabilities in an inclusive educational environment of the University using as the example the Faculty of distance learning of MSUPE. It is shown that the active model of disability aimed at fostering students’ own activity may become a basis of psychological and pedagogical support for university students with disabilities. Psychological and pedagogical support of students with disabilities includes a variety of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The studies have also demonstrated a higher level of psychological well-being, the advantage of constructive coping strategies over non-constructive ones both of students with disabilities and of healthy peers in the inclusive distance learning environment. At the same time, the authors note that students with disabilities do not sufficiently recognize their value as a person, are less confident in themselves and in their capabilities, often inadequately assess the opinions of others about themselves, and misinterpret the reactions of others about themselves, which, according to the authors, testifies about the insufficient level of selfacceptance [20].…”
Section: The Objective Of the Workmentioning
confidence: 99%
“…The studies have also demonstrated a higher level of psychological well-being, the advantage of constructive coping strategies over non-constructive ones both of students with disabilities and of healthy peers in the inclusive distance learning environment. At the same time, the authors note that students with disabilities do not sufficiently recognize their value as a person, are less confident in themselves and in their capabilities, often inadequately assess the opinions of others about themselves, and misinterpret the reactions of others about themselves, which, according to the authors, testifies about the insufficient level of selfacceptance [20].…”
Section: The Objective Of the Workmentioning
confidence: 99%